Optimalisasi Kinerja Perusahaan Melalui Manajemen Organisasi - RACHMAWATI, DITA; SETYO WARDANI, WIWIT (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2025)
This study aims to determine some of the advantages of the Duta Dainur Printing service company towards customer satisfaction. In this modern era, with the increasing development of technology, more and more people need printing services, especially students and pupils. In this case, Duta Dainur Printing carries out several competitive advantage strategies to develop and assess its company, such as providing the best possible service in a friendly and polite manner. This is done to increase customer satisfaction so that they can subscribe to Duta Dainur Printing. This study uses primary data by distributing questionnaires to 32 subscribed populations in Malang.